2019
DOI: 10.3390/ijms20205240
|View full text |Cite
|
Sign up to set email alerts
|

Fusaricidin Produced by Paenibacillus polymyxa WLY78 Induces Systemic Resistance against Fusarium Wilt of Cucumber

Abstract: Cucumber is an important vegetable crop in China. Fusarium wilt is a soil-borne disease that can significantly reduce cucumber yields. Paenibacillus polymyxa WLY78 can strongly inhibit Fusarium oxysporum f. sp. Cucumerium, which causes Fusarium wilt disease. In this study, we screened the genome of WLY78 and found eight potential antibiotic biosynthesis gene clusters. Mutation analysis showed that among the eight clusters, the fusaricidin synthesis (fus) gene cluster is involved in inhibiting the Fusarium genu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 62 publications
(73 reference statements)
0
41
0
Order By: Relevance
“…Fusaricidins and the single fus operon encoding a nonribosomal peptide synthetase ( fusA ) for the biosynthesis of a variety of fusaricidins ( Han et al, 2012 ) have been demonstrated to play roles in P. polymyxa against broad-spectrum fungal pathogens ( Choi et al, 2008 ; Li et al, 2013 ; Li and Chen, 2019 ). Fusaricidins produced by P. polymyxa have been demonstrated to inhibit Fusarium spore germination and disrupt hyphal membranes ( Li and Chen, 2019 ). Likely, fusaricidins are responsible for the damage of Fusarium hyphal cells by P. peoriae RP51 found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusaricidins and the single fus operon encoding a nonribosomal peptide synthetase ( fusA ) for the biosynthesis of a variety of fusaricidins ( Han et al, 2012 ) have been demonstrated to play roles in P. polymyxa against broad-spectrum fungal pathogens ( Choi et al, 2008 ; Li et al, 2013 ; Li and Chen, 2019 ). Fusaricidins produced by P. polymyxa have been demonstrated to inhibit Fusarium spore germination and disrupt hyphal membranes ( Li and Chen, 2019 ). Likely, fusaricidins are responsible for the damage of Fusarium hyphal cells by P. peoriae RP51 found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Liu et al (2019) showed that all isolated nitrogen-fixing strains within the P. polymyxa complex ( n = 20) inhibited the growth of four or over four of six tested phytopathogenic fungi whereas other five strains outside of the P. polymyxa complex did not inhibit any of the six tested fungi. Fusaricidins produced by P. polymyxa have also been demonstrated to induce plant systemic resistance via salicylic acid pathway against Fusarium and Phytophthora pathogens ( Lee et al, 2013 ; Li and Chen, 2019 ). Therefore, the P. polymyxa complex is a promising resource for fusaricidin-dependent control of broad-spectrum fungal pathogens and inducing plant systemic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some studies on the application of P. polymyxa in the control of F. oxysporum . For example, P. polymyxa NSY50 can significantly up-regulate the expression level of defense related genes PR1 and PR5 in cucumber roots at the early stages upon challenge with FOC [ 13 ], P. polymyxa WLY78 can strongly inhibit fusarium wilt of cucumber [ 25 ], NSY50 and WLY78 can improve the resistance of cucumber to FOC, and also have direct control effect on FOC. Some P. polymyxa strains were able to inhibit the growth of F. oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also found that most core microbes in the tubers and rhizosphere had plant growth-promoting potential. These core genera are known to produce various antibiotics, including bacillibactin and lipopeptides (produced by Bacillus ) ( Li et al, 2014 ; Liu et al, 2017 ), 2, 4-diac-etylphlor-oglucinol and phenazines (produced by Pseudomonas ) ( Mazurier et al, 2009 ; Hu et al, 2017 ), fusaricidin (produced by Paenibacillus ) ( Finch et al, 2018 ; Li and Chen, 2019 ), and thiopeptide and ectoine (produced by Streptomyces ) ( Cha et al, 2016 ). Overall, identifying these core and unique microbiomes is important for understanding the responsive microbial components associated with different plant genotypes.…”
Section: Discussionmentioning
confidence: 99%